Colonial governance and resource allocation in the British West Indies (1838-1938) - Luisito Bertinelli; Fabio Gatti; Eric Strobl (European Historical Economics Society (EHES), 2025)
Plantation elites continued to dominate local colonial governments in the British West Indies even after the abolition of slavery in 1834, directing public spending towards maintaining public order and protecting their property. As such they resisted any reforms that threatened their power, while the local non-white population, constituting of over 90% of the colonies' inhabitants, faced repression, segregation, and limited support. A pivotal shift occurred following the 1865 Morant Bay Rebellion in Jamaica, which prompted Britain to intervene so that by the 1870s most of the West Indian Assemblies were abolished, and the Colonial Office in London assumed direct control of colonial governance. This paper investigates how this shift from the Old Representative System to Crown Colony rule affected government resource allocation. Using public finance data from 16 British West Indian colonies between 1838 and 1938 we demonstrate that the governance reforms led to a significant reallocation of public expenditure towards welfare spending, as well as infrastructure and agricultural development. Our findings contribute to the economic history of colonial governance by revealing how Britain's political intervention fostered expenditures not necessarily in the interests of the planter oligarchy, thereby promoting a broader modernization of British West Indian economies.
Keywords: H1 H5 N00 N3 O1; 330; Economic History; Colonialism; Political Economics; Public Economics